PENGARUH DISIPLIN, KOMPETENSI SDM DAN KARAKTERISTIK PEKERJAAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN TAPANULI TENGAH - Amaludin Sikumbang; Jumali Jumali; Ramadhan Siregar; Lasmaria Saragi; Azizza Azizza (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
The formulation of the problem in this study is whether discipline, HR competence and job characteristics simultaneously have a positive and significant effect on the work productivity employees at Education Office of Central Tapanuli Regency. This study aims to determine the effect of discipline, HR competence and job characteristics on the work productivity employees at Education Office of Central Tapanuli Regency. The sample in this study were all employees at Education Office of Central Tapanuli Regency, amounting to 56 people. The data analysis technique in this research is Multiple Linear Regression. The results of this study indicate; Discipline partially has a positive and significant effect on employee work productivity; Human resource competence partially has a positive and significant effect on employee work productivity; Job characteristics partially have a positive and significant effect on employee work productivity; Discipline, HR competence and job characteristics simultaneously have a positive and significant effect on employee work productivity